Low Back Pain Pada Petani Karet: Sebuah Tinjauan Pustaka - Redi Bintang Pratama; Muhammad Aditya Utomo; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders experienced by agricultural workers, including rubber farmers, due to heavy physical demands, repetitive activities, and non-ergonomic work postures. The high prevalence of LBP among rubber farmers has the potential to reduce work productivity, increase the risk of disability, and negatively impact quality of life. This study aims to review the literature related to the incidence, prevalence, risk factors, and prevention and management efforts for Low Back Pain in rubber farmers. The method used is a literature review by searching for scientific articles through the Google Scholar, PubMed, ScienceDirect, and Garuda databases. The articles included were original studies in Indonesian and English published in the last ten years and discussed LBP in rubber farmers or agricultural workers with similar work characteristics. The results of the study showed that the prevalence of LBP among rubber farmers was relatively high, ranging from 33% to more than 70%. The main risk factors include heavy workloads, non-ergonomic work postures, repetitive work activities, prolonged standing or bending, and working without ergonomic training. Individual factors such as age, length of service, body mass index, and smoking habits also contribute to an increased risk of LBP. Recommended LBP prevention and management efforts include applying ergonomic principles at work, regulating work and rest times, occupational health education, stretching and back muscle strengthening exercises, and controlling individual risk factors. The conclusion of this literature review indicates that LBP among rubber farmers is a multifactorial occupational health problem that requires ergonomic interventions and continuous occupational health promotion.